The effect of language structures in social event attribution among L2 English learner - Chengping Xu; Xiangru Meng (Acta Psychologica)
This article investigates whether English positive-negative alternating causal clauses and active-passive alternating syntactic structures make a difference in social event attribution of Chinese-L1 English-L2 learners. Results of sentence completion tasks show that there is no across-the-board language effect on attribution tendencies to the patient, the agent and the interactive parties, which are the constituents of the target sentences, but passive structures induce more attribution to the patient than its counterparts, and that L2 learners exhibit a gradience of attribution preferences for the patient, followed by the agent and the interactive parties in whichever clause or syntactic conditions. The causal reasoning patterns found in this study failed to support the claim of Linguistic Relativity, while validating the hypothesis regarding the patient-directed Causal Asymmetry Bias. Results are discussed with respect to the relationship between language and thought.